Relationship of Purchase Interest, Price and Purchase Decisions to IMEI Policy (Literature Review Study) - Saputra, Farhan; M Ridho Mahaputra (Journal of Law, Politic and Humanities, 2022)
The Literature Review article on the Relationship of Buying Interest, Price and Purchase Decision to IMEI Policy is a scientific article that aims to build research hypotheses regarding the influence between variables used in further research, within the scope of Marketing Management. The method of writing this Literature Review article is the library research method, which is sourced from online media such as Google Scholar and sourced from other academic online media and uses Mendeley as a bibliography reference. The results of this Literature Review article are: 1) Buying Interest is related to IMEI Policy; 2) Price is related to IMEI Policy; and 3) Purchase Decision related to IMEI Policy. Apart from the 3 independent variables related to the dependent variable, there are other factors, namely Brand Image, Sales and Promotion.